ナンキョク ドライバレー チイキ ノ エンルイ セキシュツブツ ニ ツイテ - 西山, 孝; ニシヤマ, タカシ; NISHIYAMA, Takashi (国立極地研究所, 1977)
P(論文) ドライバレーに産出する塩類析出物について,X線回折分析法により鉱物の同定を行い,水平的および垂直的な分布の相違を検討した.同定された鉱物は,地表からの試料では炭酸塩5種,硫酸塩5種,硝酸塩2種,ハロゲン化物2種で,ボーリソグコアーからの試料では炭酸塩1種,沸石2種,ハロゲン化物2種,緑泥石1種であった. これらの塩類析出物は産出個所により異なり,一般に炭酸塩はテイラー谷に,硫酸塩はライト谷に多い傾向があり,とくに炭酸ソーダ石,サーモナトライト,モノハイドロカルサイトの産出がテイラー谷の海岸に近い部分に限られていること,チリ硝石,ダブラスカイト,ブレーダイトがライト谷にのみ晶出していることは顕著な特徴であった. 次に塩類析出物の分布と湖水の化学成分とを比較検討した結果,一部には熱水起源と考えられる塩類析出物もあるが,多くの塩類の起源は海水あるいは風送塩によるものと推察された. The areal and vertical distributions of evaporite minerals in the Taylor Valley and the Wright Valley were studied with X-ray diffraction techniques to disclose the origins of salts. Halite, sylvite. thenardite. mirabilite. Gypsum, calcite, aragonite, trona, thermonatrite, monohydrocalcite, soda niter, bloedite, and drapskite were identified in specimens on the ground surface, and calcite, fluorite, laumontite, chahay.ite. antarcticite, and chlorite in core samples. In general, carbonate minerals predominate in the Taylor Valley, while sulphate minerals, except thenardite, predominate in the Wright Valley. Halite and thenardite are widespread in both areas. Trona, thermonatrite, and monohydrocalcite are found exclusively in the eastern Taylor Valley, and soda niter, bloedite, and drapskite in the Wright Valley. There is a general trend for sulphate minerals to be concentrated in elevated areas, and carbonate minerals in low areas. From a comparison of the distribution of these salts and the chemical composition of lake water in the area, it seems that the main sources of salts distributed in the Taylor Valley and the Wright Valley are of marine and/or wind-transported origins, and that based on the nature of minerals from core samples, a small amount of salts is formed from hydrothermal solution. departmental bulletin paper